The circle of reason - Ghosh, Amitav (Pemanen lake & Ravi Dayal, 1986)
In a vivid and magical story, this novel traces the misadventures of Alu, a young master weaver in a small Bengali village who is falsely accused of terrorism. Alu flees his home, traveling through Bombay to the Persian Gulf to North Africa with a bird-watching policeman in pursuit.